2020
DOI: 10.1002/mco2.17
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene antagonizes lead toxicity by reducing mitochondrial oxidative damage and mitochondria‐mediated apoptosis in cultured hippocampal neurons

Abstract: Lead (Pb) exhibits serious adverse effects on the central nervous system, and the major pathogenic mechanism of Pb toxicity is oxidative stress. As one of the carotenoid family members with potent antioxidant properties, lycopene has shown its protections by inhibiting oxidative stress damage in numerous models of neurotoxicity. The current study was designed to explore the possible protective property in primary cultured rat hippocampal neurons challenged with Pb. We observed that 5 M lycopene pretreatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…The sections were stained using the TUNEL assay staining kit (Roche, Germany) according to the manufacturer's protocol and previous study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sections were stained using the TUNEL assay staining kit (Roche, Germany) according to the manufacturer's protocol and previous study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that exposure to AFB1 significantly elevates the Bax/Bcl-2 protein ratio, enhances caspase-9 and caspase-3 activities, and increases their mRNA expressions, ultimately resulting in cell apoptosis in HepG2 cells, IMR-32 cells (a neuroblastoma cell line), as well as in the brain, spleen, liver, and renal tissues of animals [26,80,[133][134][135]. Numerous studies have indicated that lycopene supplementation can effectively mitigate apoptotic cell death induced by colistin, tert-butyl hydroperoxide, and lead through the inhibition of mitochondrial dysfunction and the mitochondrial pathway [94,136,137]. Consistent with these findings, researchers have observed that lycopene supplementation at different doses can successfully attenuate AFB1 exposure-induced cell apoptosis, as evidenced by the suppression of cytoplasmic CytC, Bax, and cleaved caspase-3 proteins' expression, as well as the activities and mRNA expression of caspases-3 and -9, and the upregulation of Bcl-2 protein [26,47,87,138].…”
Section: Inhibition Of Mitochondrial Dysfunction and Apoptosismentioning
confidence: 99%
“…Positron emission tomography implemented by a pilot study has revealed that altering the distribution of a mitochondrial translocator protein in the brain significantly affects the cognitive functions of SLE patients ( 139 ). The microglia cells are stimulated by pro-inflammatory cytokines to cause impairment in axonal transmission and mitochondrial dysfunction ( 140 , 141 ). The swollen and vacuolated mitochondria cause Ca 2+ dysregulation and caspases signal activation ( 140 , 142 ).…”
Section: Mitochondrial Dysfunction Damages Organsmentioning
confidence: 99%